Fabrication of g-C3N4/transition metal (Fe, Co, Ni, Mn and Cr)-doped ZnO ternary composites: Excellent visible light active photocatalysts for the degradation of organic pollutants from wastewater. (March 2022) - Qamar, Muhammad Azam; Javed, Mohsin; Shahid, Sammia; Sher, Mudassar
Highlights: Fabrication of g-C3 N4 /metal doped-ZnO hybrid composite by chemical co-precipitation method. Band gap tuning of ZnO by simultaneous doping it with transition metals (Cr, Fe, Mn, Co & Ni) and hybridizing with g-C3 N4 . g-C3 N4 /Mn doped-ZnO ternary composite exhibits better photocatalytic efficiency than other g-C3 N4 /(Cr, Fe, Co & Ni) doped-ZnO composites. Photocatalytic MB degradation rate of g-C3 N4 /Mn doped-ZnO is 7 times higher than other g-C3 N4 /ZnO and 16 times higher than ZnO. Hybrid composite g-C3 N4 /Mn-ZnO exhibits excellent recyclability and sustainability. Abstract: This study investigated the comparative photocatalytic efficiency of metal (Fe, Co, Ni, Mn and Cr)-doped ZnO/g-C3 N4 nanocomposites against MB dye. The materials were synthesised via the chemical co-precipitation method and characterised by critical analytical techniques. TEM results revealed the distinctive heterojunctions developed between g-C3 N4 and metal-doped ZnO. Optical and photoelectrochemical analysis of the synthesised g-C3 N4 /metal-doped ZnO exhibited a redshift in light absorption and decay in electron-hole pairs recombination rate, respectively. The increase in the photocatalytic activity of the synthesised nanocomposites might be attributed to the development of exemplary interfaces between ZnO, g-C3 N4 and metal dopants. In particular, g-C3 N4 /Mn-doped ZnO nanocomposites (MnGZ NCs) exhibited maximum photocatalytic degradation of MB (100%) after 60 min of sunlight irradiations. The MnGZ NCs showed good photocatalytic stability even after 12 consecutive cycles. The photoluminescence and reactive species scavenger test results suggest a potential MB degradation mechanism over the MnGZ NCs. Graphical abstract: Image, graphical abstract